ANALISIS PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA MANAJERIAL DENGAN GAYA KEPEMIMPINAN, SISTEM PENGUKURAN KINERJA, DAN SISTEM PENGHARGAAN SEBAGAI VARIABEL MODERATING - Muslikun .; Riana Sitawati; Sutono . (LPPM STIE DHARMAPUTRA SEMARANG, 2016)
This study examined the influence of Total Quality Management ( TQM ) to managerial performance in the style of leadership , performance measurement system , and reward systems as moderating variables on the non-profit organization Yayasan Al Ishlah Insan Mulia ( YAIIM ) Wonosobo. The sample used in this study is the top, middle and lower level managers who work in institutions under YAIIM Wonosobo. Questionnaires were distributed as many as 28 copies, with saturated sampling technique so that the entire population can be used as a sample research and interviews for 5 organizatons leader. The analytical tool used is multiple regression analysis and regression analysis moderation. Based on the results of the t test for TQM showed a significance value of 0.036 >0.05 , meaning the application of TQM significantly influence managerial performance. Variations leadership style showed a significance value of 0.494> 0.05, a performance measurement system showed a significance value of 0.180 <0.05, and measurement systems showed a significance value of 0.209 <0.05, mean TQM moderated by leadership style, performance measurement system, and the system award no significant influence on managerial performance. The failure is due to the moderating variable leadership style compound, the object characteristic non-profit organizations - foundations, motivation and dedication of service, and the time factor in the application of management accounting system..Keywords::Total Quality Management ( TQM ) , leadership style , performance measurement systems , reward systems , and managerial performance, and non-profit organization - foundations.